2021
DOI: 10.3390/met11040586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen on the Tensile Behavior of Austenitic Stainless Steels 316L Produced by Laser-Powder Bed Fusion

Abstract: Hydrogen was doped in austenitic stainless steel (ASS) 316L tensile samples produced by the laser-powder bed fusion (L-PBF) technique. For this aim, an electrochemical method was conducted under a high current density of 100 mA/cm2 for three days to examine its sustainability under extreme hydrogen environments at ambient temperatures. The chemical composition of the starting powders contained a high amount of Ni, approximately 12.9 wt.%, as a strong austenite stabilizer. The tensile tests disclosed that hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The twins can help to maintain strain hardening at higher stress levels, resulting in higher ductility [ 40 ]. However, the sample with H did not form high-density twins, which could be an important reason for the reduction in UTS and ductility of the samples with H. The surface damage induced by hydrogen will cause mechanical property degradation [ 14 ]. As shown in the SEM pictures of the hydrogen charging sample ( Figure 3 d,e), the hydrogen-induced cracking along the MPBs, which will be conducive to generating high-stress concentration, resulting in faster failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The twins can help to maintain strain hardening at higher stress levels, resulting in higher ductility [ 40 ]. However, the sample with H did not form high-density twins, which could be an important reason for the reduction in UTS and ductility of the samples with H. The surface damage induced by hydrogen will cause mechanical property degradation [ 14 ]. As shown in the SEM pictures of the hydrogen charging sample ( Figure 3 d,e), the hydrogen-induced cracking along the MPBs, which will be conducive to generating high-stress concentration, resulting in faster failure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have investigated the hydrogen behavior of selective laser-melted austenitic stainless steel. Khaleghifar et al [ 14 ] found that SLM 316L SS has a slight reduction in elongation after H charging. Bertsch et al [ 15 ] systematically investigated the influence of hydrogen on the mechanical properties of SLM 316L SS, indicating that the presence of hydrogen leads to decreasing plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the thickest strut, T1.4, displayed fewer surface flaws, the mechanical properties were more affected by H-charging. This can be attributed to reversible trapping sites, such as dislocation cores [ 23 ], which are increased with increasing cross-section, as reported in the literature [ 38 , 39 ]. This is in an agreement with the mechanical properties illustrated in Table 2 .…”
Section: Discussionmentioning
confidence: 84%
“…There are two competing factors which affect the HE susceptibility of AM316L SS: the surface roughness and the hydrogen trapping sites [ 19 , 20 , 21 , 22 , 23 , 45 ]. Hydrogen atoms effectively diffuse into the rough surface as the surface flaws and other imperfections, such as pores, serve as entrances for the H atoms, as reported in the literature [ 24 , 44 , 45 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation